ROHINGYA CRISIS: ASEAN's RESPONSES ANALYSIS IN THE LIBERALISM THEORY - Syarifah Dinda Nuraini Alkadrie; Alderin Joisafita Tangdialla; Andi Anugrah Saputra; Oilinia Miyanda Maruhawa (Sociae Polites, 2019)
The Rohingya ethnicity in Myanmar abused in 2016 reflected an act of violence against Rohingya Muslims by the Myanmar armed forces and police. To manage conflicts that extend the humanitarian crisis in Myanmar, the role of governments is important. Because of the abuse and the complex types of human rights abuses of the Rohingya ethnicity, researchers took Rohingya ethnicity into our case study in this paper. Researchers also use the theory of Liberalism and focus on the response and the actions of ASEAN countries that are a place for these Rohingya refugees. On the actions, ASEAN has taken in the context of Liberalism. These researches use the qualitative method of analysis. Due to the data analysis, security policies consider the domestic interests of each country, which Rohingya refugees are supposed to be able to get help. Keywords: ASEAN, Rohingya, Myanmar, Refugees, Liberalism.